Analysis of Leakage Current Calculation Through Thermal Failure Voltage on 150/20 kV Transformers in GIS Simpang, Surabaya - Widagdo, Reza Sarwo; Andriawan, Aris Heri; Suri Tauladan, Imam; Ivan Maulana, Ade (Politeknik Caltex Riau, 2024)
In the current test, leaks really need to be carried out at GIS Simpang. This test was carried out by strengthening the 20 kV incoming cable in the GIS Simpang 150/20 kV transformer bay. The impact of measuring this leakage current is to reduce the occurrence of leakage currents so that they are not too severe because this can determine how much the leakage current increases in the incoming cable. The trend test results were measured to determine the comparison between the leakage current in January and the leakage current measurement process at GIS Simpang. Based on the results of leakage current testing on transformer 1 and transformer 2 incoming 20 kV cables from several phases, it shows that the results of the leakage current trend in the cables have not increased significantly. However, from the calculation results listed, it can be seen from the comparison table that the results have increased during the calculation and have slight differences compared to the leakage current measurement results themselves. This is because from the calculation results, the cable temperature detection experienced a slight increase in the cable temperature as measured by thermovision to determine the thermal failure voltage. However, the cable is still suitable for operation because the temperature of the cable itself has a standard that does not exceed 150C for several measured cable phases.